Research progress on in-situ catalytic hydrodeoxygenation of lignin - ZHAO Yuying; ZHAN Jiahui; HU Rui; LUO Gang; ZHANG Shicheng* (能源环境保护)
The development of renewable energy and carbon neutrality is imperative due to the depletion of fossil fuels and environmental pollution. Lignin, as the abundant natural aromatic polymer, can be converted into high-value chemicals and fuels, offering an alternative to fossil resources. The bio-oil and chemicals generated from lignin depolymerization have limited direct applications due to their high oxygen content. The strategy of hydrodeoxygenation (HDO) provides a pathway for the devel opment of high-value biobased fuels and chemicals. However, the traditional lignin conversion process, which is dominated by high-pressure molecular hydrogen, poses safety hazards, hindering its industrial promotion. In-situ catalytic HDO of lignin can be an alternative strategy. It utilizes solvents or lignin′s functional groups as hydrogen sources. During the catalytic process, hydrogen is generated in situ and acts on the substrate, achieving efficient value-added conversion. This method not only effectively avoids the need for external high-pressure hydrogen supply but also enables in-situ upgrading of lignin under mild conditions, improving atomic utilization and product selectivity. Through the study of in-situ catalytic HDO strategies for lignin, the research progress of in-situ hydrogen supply in recent years is summarized. The analysis includes the reaction mechanisms of four commonly used in-situ catalytic HDO strategies: combined reforming and HDO (RHDO), combined metal hydrolysis and HDO process (HHDO), catalytic transfer hydrogenation (CTH), and self-supported hydrogenolysis (SSH). The status of various strategies is discussed, and the research focus, challenges, and prospects of in-situ catalytic HDO strategies for lignin are explored.